Could the United States benefit from a lockdown? A cost-benefit analysis - Anna Scherbina (American Enterprise Institute (AEI), 2021)
Although COVID-19 vaccines are finally available, the rate at which they are administered is slow, and in the meantime the pandemic continues to claim about as many lives every day as the 9/11 tragedy. I estimate that with the promised rate of vaccinations, if no additional nonpharmaceutical interventions are implemented, 406 thousand additional lives will be lost and the future cost of the pandemic will reach 2.4 trillion, or 11% of GDP. Using a cost-benefit analysis, I assess whether it is optimal for the United States to follow the lead of many European countries and introduce a nation-wide lockdown. I find that a lockdown would be indeed optimal and, depending on the assumptions, it should last between two and four weeks and will generate a net benefit of up to 1.2 trillion.
Keywords: A; 330; COVID-19; Pandemic Curve; Cost-Benefit Analysis; Non-Pharmaceutical Interventions; Public Health Policy; Lockdown